Impact of the Protein Data Bank on antineoplastic approvals. Issue 5 (May 2020) - Westbrook, John D.; Soskind, Rose; Hudson, Brian P.; Burley, Stephen K.
Highlights: Protein Data Bank (PDB) provides open access to >160 K 3D structures of biomolecules. 79 anticancer NMEs with known molecular targets were approved by the FDA 2010–2018. PDB provides target structures for >90% of anticancer NMEs approved 2010–2018. PDB provides target–NME co-structures for >50% anticancer NMEs approved 2010–2018. PDB facilitated discovery and development of >90% anticancer NMEs approved 2010–2018. Abstract : Open access to 3D structure information from the Protein Data Bank (PDB) facilitated discovery and development of >90% of the 79 new antineoplastic agents (54 small molecules, 25 biologics) with known molecular targets approved by the FDA 2010–2018. Analyses of PDB holdings, the scientific literature and related documents for each drug–target combination revealed that the impact of public-domain 3D structure data was broad and substantial, ranging from understanding target biology (∼95% of all targets) to identifying a given target as probably druggable (∼95% of all targets) to structure-guided lead optimization (>70% of all small-molecule drugs). In addition to aggregate impact assessments, illustrative case studies are presented for three protein kinase inhibitors, an allosteric enzyme inhibitor and seven advanced-stage melanoma therapeutics. Teaser: Open access to 3D macromolecular structure information managed by the Protein Data Bank facilitated discovery and development of >90% of new antineoplastic agents approved by the FDA 2010–2018.